O comércio eletrônico e sua aplicação no planejamento e gestão do processo de compras da cadeia de suprimentos: um estudo na indústria química - Castilho Júnior, Newton Corrêa de (2002)
Not long after addressing integration issues for its internal functions, the enterprise faces a new challenge. It turns itself to the outside, to create a networked environment, that includes its business partners. It becomes crucial, that improvements to partnering relationship be achieved, by means of automated processes, that manage their Supply and Distribution Chains. The Information Technology, by allowing processes connection and systems interaction, becomes an essential tool for this transformation. Specifically, the environment built over the Information Highway, formed by the Internet and its services, as the WWW, assures considerable relationship leverage within the organization, among organizations and between them and its customers. This business transformation, based on the Information Technology, over communication networks, we call Electronic Commerce. Based on the knowledge brought by the currently available theory and also on the results attained by the case study performed, the author identifies and categorizes the Electronic Commerce influences over the Supply Chain buying processes for the chemical industry, while structuring these influences and their relations to the existing digital business models